2006
DOI: 10.2147/copd.2006.1.2.99
|View full text |Cite
|
Sign up to set email alerts
|

The role for N-acetylcysteine in the management of COPD

Abstract: Oxidative stress has been implicated in the pathogenesis and progression of COPD. Both reactive oxidant species from inhaled cigarette smoke and those endogenously formed by inflammatory cells constitute an increased intrapulmonary oxidant burden. Structural changes to essential components of the lung are caused by oxidative stress, contributing to irreversible damage of both parenchyma and airway walls. The antioxidant N-acetylcysteine (NAC), a glutathione precursor, has been applied in these patients to redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
1
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 56 publications
2
59
1
6
Order By: Relevance
“…Treatment with NAC in humans changes the pulmonary oxidanteantioxidant imbalance. 29 Sadowska et al 30 showed that long-term oral administration of NAC reduces H 2 O 2 formation in the airways of COPD patients and that there is evidence of antioxidant action of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with NAC in humans changes the pulmonary oxidanteantioxidant imbalance. 29 Sadowska et al 30 showed that long-term oral administration of NAC reduces H 2 O 2 formation in the airways of COPD patients and that there is evidence of antioxidant action of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…The low efficiency of NAC shown in the BRONCUS trial might be explained by the relatively low dose (600 mg once daily) used in that study [95]. Other studies such as Idiopathic Pulmonary Fibrosis International Group Exploring N-Acetylcysteine I Annual (IFIGENIA) study have suggested that 600 mg twice daily is safe and more effective [100].…”
Section: N-acetylcysteinementioning
confidence: 91%
“…Some systematic reviews and meta-analyses have suggested that NAC prevents exacerbations and improves symptoms in Chronic obstructive pulmonary disease (COPD) patients [94][95][96][97][98] (Table 2), however, probably with little or no effect on the lung function parameters [96].…”
Section: N-acetylcysteinementioning
confidence: 99%
“…This molecule reduces the number A c c e p t e d M a n u s c r i p t 5 and impact of COPD exacerbations [28] and also the inflammatory response in epithelial cells exposed to H5N1 influenza A virus [20]. Although anti-mucolitic effects of NAC are well established, little is known about its effects on the MUC5AC expression in virus models of infection.…”
Section: Introductionmentioning
confidence: 99%